PENINGKATAN KUALITAS LAYANAN PELANGGAN UMKM MELALUI IMPLEMENTASI SERVICE QUALITY DAN SOP OPERASIONAL - Uning Heri Gagarin; Yeni Trisna Purba; Yohanis Rumbiak (Jurnal Industri Kreatif dan Inovatif, 2025)
This Community Service Program (PKM) activity aims to improve the quality of MSME customer service through the application of the service quality concept and the preparation and implementation of operational service SOPs. Partner issues include inconsistent service between officers/shifts, unclear customer response standards, unstructured complaint handling, and the absence of service indicators. The program is carried out through service quality assessments (observations and short surveys), service quality dimension training, service SOP development workshops (offline/online), service and complaint simulations, and assistance with implementation trials. The main outputs are a customer service SOP package, service communication standards, monitoring forms, and simple service KPIs. Targeted outcomes include increased service consistency, reduced repeat complaints, and increased customer satisfaction.